2020
DOI: 10.1007/s00590-020-02640-3
|View full text |Cite
|
Sign up to set email alerts
|

Rare aneurysmal bone cysts: multifocal, extraosseous, and surface variants

Abstract: Multifocal, extraosseous, and surface aneurysmal bone cysts are rare variants of the primary lesions. The clinicopathological features are similar, and the optimal treatment is surgical. Although local recurrences may occur, the prognosis is excellent. This review article introduces the readers to a rare diagnosis which they may have been previously unfamiliar with, presents the clinicopathological and imaging features of these rare aneurysmal bone cyst variants, and discusses their diagnosis and treatment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
(157 reference statements)
0
5
0
Order By: Relevance
“…This variant seems to be particularly frequent in male patients (5 patients/7 in Angelini A et al's review), and the most reported sites are the femur and the tibia [8]. No case of multifocal ABC of pelvic bones was found.The multifocal forms of ABC are in the majority of cases described metachronously [5,6,8,[13][14][15], the synchronous occurrence in the same patient is exceptional. Only one case of two separate synchronous ABC of the humerus was found in Mohaidat ZM et al series [9].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…This variant seems to be particularly frequent in male patients (5 patients/7 in Angelini A et al's review), and the most reported sites are the femur and the tibia [8]. No case of multifocal ABC of pelvic bones was found.The multifocal forms of ABC are in the majority of cases described metachronously [5,6,8,[13][14][15], the synchronous occurrence in the same patient is exceptional. Only one case of two separate synchronous ABC of the humerus was found in Mohaidat ZM et al series [9].…”
Section: Discussionmentioning
confidence: 93%
“…There are two types of multifocal ABC: mono-ostotic multifocal ABC when multiple cystic tumors occur in the same bone and poly-ostotic multifocal ABC when multiple lesions occur in multiple bones [8,15]. This variant seems to be particularly frequent in male patients (5 patients/7 in Angelini A et al's review), and the most reported sites are the femur and the tibia [8]. No case of multifocal ABC of pelvic bones was found.The multifocal forms of ABC are in the majority of cases described metachronously [5,6,8,[13][14][15], the synchronous occurrence in the same patient is exceptional.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations